Estimasi Arah Strike menggunakan Metode Resistivitas Konfigurasi Persegi - Cahyono, Agung; Yulianto, Gatot (BERKALA FISIKA, 2007)
The sounding square array resistivity method had been used to estimate strike orientation in a sub surface anomaly model. The advantage of square array are more sensitif in an anisotropic medium such as strike than inline array. Strike is an important factor to placed an array configuration in resistivity method. The array commonly lay down paralel or perpendicular with a strike depend on anomaly structure. The mapping square array was used to detect the model anomaly.The sounding square array were measured by rotating array with azimuth ,,,Â and . The sounding square array had an electrode spacing 1 m, 1,4 m, 2 m and 2,8 m. Azimuthal apparent resistivity wasÂ  obtained by calculation and then was plotted into Rossete diagram. The estimation of strike orientation was determined perpendicularly from maximum azimuthal apparent resistivity. The mapping square array used 10 m array spacing with 1 m electrode spacing. The Wenner array used 5 m with 0,5 m electrode spacing.Strike orientation was estimated on N 90 E. This estimation was based on result each electrode spacing on the sounding square array. The existing model anomaly were detected on 5 m until 7 m on mapping square array. The result of Wenner array modeling showed that anomaly model was detected on 2,5 m until 3,5 m on N 40 W. This result showed that the sounding square array can be applied to determine strike orientation which usually exist on geological structure Keywords: square array resistivity, strike,azimuth